The Tendency of Atmospheric Temperature and Precipitation from a Viewpoint of the Climatic Variation Indices - Yamakawa Shuji; Hisamochi Ryo (Japan Climatology Seminar, 2014)
Surface air temperature (AT) and precipitation are important in studying global climate system. AT and precipitation are related with climatic variation indices, such as SOl(Southern oscillation index; Philander, 1990), PDO(Pacific decadal oscillation; Mantua, et al., 1997), AO(Arcticoscillation; Yamakawa, 2005), AAO(Antarctic oscillation; Tompson & Wallace, 2000) and QBO(quasi- biennial oscillation) which are dealt with in this study. Inoue & Yamakawa (2010) analyzed the precipitation of Asia in the warm half year. This research focuses mainly on the relation between teleconnections(Gibntz, et al., 1991) and AT. Multiple regressions are used to determine the relationships between the climatic indices and AT in summer. A multipleregression including QBO should be taken into consideration to improve summer weather forecast.